JSp-cosemanticness and JSB property of Abelian groups - Yeshkeyev, A. R.; Ulbrikht, O. I. (SOBOLEV INST MATHEMATICS, 2016)
The main purpose of this article is to study the modeltheoretic properties of Abelian groups within Jonsson theories. The obtained results give us Jonsson analogs for the Schr¨oder-Bernstein property and for the elementary classification of complete theories of Abelian groups.
Keywords: Jonsson theory; model companion; existentially closed model; perfectness; cosemanticness